Age Matching of Elderly Liver Grafts With Elderly Recipients Does Not Have a Synergistic Effect on Long-term Outcomes When Both Are Carefully Selected. Issue 4 (April 2019) - Gilbo, Nicholas; Jochmans, Ina; Sainz-Barriga, Mauricio; Nevens, Frederik; van der Merwe, Schalk; Laleman, Wim; Verslype, Chris; Cassiman, David; Verbeke, Len; van Malenstein, Hannah; Roskams, Tania; Pirenne, Jacques; et al.
Abstract : Background: Older donors and recipients are increasingly considered for liver transplantation. Both donor and recipient age have a negative impact on outcomes. Large registry analyses show that older donors are frequently matched to older recipients. Whether age-related risks accumulate in a synergic negative effect on outcomes because of donor-recipient age matching is poorly understood. Methods: We investigated the impact of donor-recipient age interaction on patient and death-censored graft survival in multivariate Cox regressions in 849 transplants (January 2000 to December 2015). Results: Donors 70 years or older did not affect long-term patient or graft survival. Recipient age independently increased the risk of death (hazard ratio [HR], 1.03; 95% confidence interval [CI], 1.02-1.05, P < 0.0001), but donor-recipient age interaction was noninfluential. The negative impact of recipient age on patient survival was significant as early as 6 months after transplantation (HR, 1.06; 95% CI, 1.03-1.09; P = 0.00008). The adjusted risk of death was significant for patients aged 60 to 69 years (HR, 1.995; 95% CI, 1.40-2.85; P < 0.0001) and 70 years or older (HR, 2.001; 95% CI, 1.10-2.66; P = 0.04). In contrast, the risk of graft loss was not influenced by recipient age (HR, 1.02; 95% CI, 0.996-1.04; P = 0.11) or age interaction. Conclusions: Older livers can be safely used in older recipients without jeopardizing graft and patient survival if other risk factors are minimized. Abstract : Supplemental digital content is available in the text.